Discretionary Policy Responses in India and Indonesia Amidst the COVID-19 Pandemic: Challenges, Strategies, and the Imperative for Legal Reform - Rumesten RS, Iza; Muntaqo, Firman; Panjaitan, Saut Parulian; Bugaeva, Anna Sergeevna; Towadi, Mellisa (Universitas Negeri Semarang, 2023)
This study endeavors to conduct a meticulous analysis and comparison of the discretionary policy frameworks employed by India and Indonesia in response to the challenges posed by the COVID-19 pandemic. The research delineates its focus into two primary dimensions: firstly, an examination of the structure and application of discretionary policies formulated by the central governments of both nations; secondly, an in-depth exploration of the challenges and strategic considerations in the local-level implementation of these policies, aligned with the dynamic nature of the pandemic. Employing a rigorous research methodology, this study entails the systematic analysis of pertinent legal and policy documents, a comprehensive review of existing literature, and a nuanced conceptual and philosophical interpretation of discretionary policies in the context of pandemic management. The findings of this research underscore the distinctive approaches undertaken by India and Indonesia in the implementation of discretionary policies. India adopts a more centralized model, whereas Indonesia pursues a decentralized trajectory. Both nations encounter challenges in inter-governmental coordination, with India grappling with the harmonization of central and state policies, and Indonesia contending with disparities between central and local governance. Furthermore, the research underscores the imperative for both countries to reassess and develop legislative frameworks that are adaptive and dynamic, harmonizing legal rigidity with the requisite flexibility to effectively respond to the rapidly evolving conditions of the pandemic. Crucially, the research emphasizes the necessity for enhanced transparency and accountability within the realm of discretionary policy. Both countries are urged to fortify these elements to cultivate public trust and ensure the efficacious and equitable implementation of policies during the ongoing public health crisis.